STRUCTURAL IDENTIFICATION OF DYNAMICS MODELS MAIN CHANNEL OF THE COURSE MEASUREMENT SYSTEM SHIP - Kasyanov , V. G.; Bezkorovainy , Yu. N.; Safronova, I. Yu. (Problems of Informatization and Management, 2021)
Structural identification of the main channel of the ship's course measuring system was made on the "pitching" simulator of the base. As a result of identification, the transfer function of the investigated tract, as well as the spectral density of the uncontrolled disturbance acting on it, were obtained.